2011
DOI: 10.1589/jpts.23.17
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pelvic Adjustment on Functional Leg Length Inequality and Foot Pressure

Abstract: Abstract. [Purpose] This study was conducted to evaluate the influence of pelvic adjustment on functional leg length inequality (FLLI) and foot pressure.[Subjects] The study subjects were 40 adults who were healthy but had FLLI of at least 10 mm. Subjects were randomly assigned to two groups, an experimental group (n=20) and a control group (n=20).[Methods] The subjects of the experimental group underwent pelvic adjustment 3 times a week for 4 weeks. A tape-measure was used to measure FLLI, and F-Scan was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Park et al reported that balance in 20 elderly men was improved through pelvic adjustment according to the Gonstead method 15 ) . In this study, FLLI was reduced after pelvic adjustment, a finding similar to a previous study in which pelvic adjustment helped reduce FLLI and the pressure difference between soles 14 ) .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Park et al reported that balance in 20 elderly men was improved through pelvic adjustment according to the Gonstead method 15 ) . In this study, FLLI was reduced after pelvic adjustment, a finding similar to a previous study in which pelvic adjustment helped reduce FLLI and the pressure difference between soles 14 ) .…”
Section: Discussionsupporting
confidence: 90%
“…Subjects were instructed to lie prone, their pelvic height was checked, and the posterior-inferior innominate bone was given an anterior-superior impact while the anterior-superior pelvis was given a posterior-inferior impact. When making these impacts, the therapist put one of his hands on top of the other, placed them on the posterior-superior iliac spine or the ischial spine, and then gave the impact using his own weight, gravity, and acceleration 14 ) . This adjustment was performed 3–5 times by one skilled physical therapist with more than 10 years of clinical experience.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Gong et al 34 ) showed that pelvic adjustment has a positive impact on functional leg length inequality and foot pressure. Park et al 35 ) reported greater stability after pelvic adjustment in an elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…Leg-length discrepancy (LLD) is the term used to describe the condition when both legs are markedly different in length 1 ) . Leg-length discrepancy occurs in 40–70% of the total population and is reported to be more than 20 mm in one out of every 1,000 persons 2 ) .…”
Section: Introductionmentioning
confidence: 99%